Robust computational method for fast calculations of multicharged ions lineshapes affected by a low-frequency electrostatic plasma turbulence. (4th January 2017) - Dalimier, E; Oks, E
Abstract: Transport phenomena in plasmas, such as, e.g., resistivity, can be affected by electrostatic turbulence that frequently occurs in various kinds of laboratory and astrophysical plasmas. Transport phenomena are affected most significantly by a low-frequency electrostatic turbulence—such as, e.g., ion acoustic waves, also known as ionic sound—causing anomalous resistivity. In this case, for computing profiles of spectral lines, emitted by plasma ions, by any appropriate code for diagnostic purposes, it is necessary to calculate the distribution of the total quasistatic field. For a practically important situation, where the average turbulent field is much greater than the characteristic ion microfield, we develop a robust computational method valid for any appropriate distribution of the ion microfield at a charged point. We show that the correction to the Rayleigh distribution of the turbulent field is controlled by the behavior of the ion microfield distribution at large fields —in distinction to the opposite (and therefore, erroneous) result in the literature. We also obtain a universal analytical expression for the correction to the Rayleigh distribution based on the asymptotic of the ion microfield distribution at large fields at a charged point. By comparison with various known distributions of the ion microfield, we show that our asymptotic formula has a sufficiently high accuracy. Also exact computations are used to verify the high accuracy of the method. This robust approximate, but accurate method yields faster computational results than the exact calculations and therefore should be important for practical situations requiring simultaneous computations of a large number of spectral lineshapes (e.g., for calculating opacities)—especially for laser-produced plasmas.